Delayed diagnosis of lymphogranuloma venereum-associated colitis in a man first suspected to have rectal cancer. (December 2016) - Bancil, Aaron S; Alexakis, Christopher; Pollok, Richard
Lymphogranuloma venereum-associated colitis is a diagnosis that should not be missed. The following case represents the importance of a thorough history, including the importance of the sexual history to prevent the misdiagnosis of these patients.